To What Extent Do Practitioners Need to Treat Stereotypy During Academic Tasks?. Issue 2 (March 2020) - Cook, Jennifer L.; Rapp, John T.
Researchers frequently argue that a child's engagement in stereotypy may compete with his ability to acquire academic skills, engage in appropriate social interactions, or both; however, few studies have directly tested these suppositions. We used a five-phase assessment to evaluate the extent to which behavioral interventions with a progressively greater number of components were necessary to decrease stereotypy and increase correct responding during academic instructions for five children diagnosed with autism spectrum disorders. For one participant, stereotypy decreased when instructors provided standard instruction without specific intervention for stereotypy. For two participants, stereotypy decreased when instructors provided standard instruction plus antecedent intervention for stereotypy with continuous music. For another participant, stereotypy decreased when instructors provided enhanced consequences for correct responding during standard instruction without either antecedent or consequent intervention for stereotypy. For the final participant, stereotypy decreased and correct responding increased when instructors provided standard instruction and consequent intervention for stereotypy.